Factors related to medical students’ and doctors’ attitudes towards older patients: a systematic review - Rajvinder Samra; Tom Cox; Adam Gordon; Simon Conroy; Mathijs Lucassen; Amanda Griffiths (2017)
studies have sought to identify the possible determinants of medical students' and doctors' attitudes towards older patients by examining relationships with a variety of factors: demographic, educational/training, exposure to older people, personality/cognitive and job/career factors. This review collates and synthesises these findings.